Corporate Social Responsibility (CSR) and Contributions Towards Society Amid Covid-19 Pandemic in Indonesia - Rosilawati, Yeni (Technium Social Sciences Journal, 2021)
The escalation of the contagious pandemic of Covid 19 has reached more than 180 countries. The Covid-19 virus initially spread in Wuhan, China. As of 17 February 2021, the Government of the Republic of Indonesia has reported 1.243.646 persons with confirmed COVID-19. There have been 33.788 deaths related to COVID-19 reported and 1.047.676 patients have recovered from the coronavirus. This paper would like to describe the practices of Corporate Social Responsibility (CSR) from the big three companies in Indonesia which are PT Pertamina (Persero), PT Adaro Energy Tbk (Adaro), and PT Aplikasi Karya Anak Bangsa (Gojek), and their contributions during the Covid-19 pandemic towards society in Indonesia. The research methodology for this article is case study with data collection based on secondary sources. Using case study method, this research studying specific phase of those three companies. The data include the review of the CSR reports was collected from companies’ websites and the clippings from online mass media. The research found that many initiatives of CSR have been conducted by companies in Indonesia to mitigate and to help the government and society affected by Covid-19. CSR activities are conducted in various ways such as assistance in the form of medical equipment, staple goods package, mobile devices, internet quota, and community development with some training and coaching in entrepreneurship. The involvement of many parties, especially companies, governments, and communities to fight the Covid-19 pandemic has created a new culture in society in the form of participative and collaborative culture which makes it easier to achieve a stable condition in the Covid-19 pandemic.